A family-specific linkage analysis of blood lipid response to fenofibrate in the Genetics of Lipid Lowering Drug and Diet Network. Issue 10 (October 2015) - Hidalgo, Bertha; Aslibekyan, Stella; Wiener, Howard W.; Irvin, Marguerite R.; Straka, Robert J.; Borecki, Ingrid B.; Tiwari, Hemant K.; Tsai, Michael Y.; Hopkins, Paul N.; Ordovas, Jose M.; Arnett, Donna K.
Abstract : Cost-effective identification of novel pharmacogenetic variants remains a pressing need in the field. Using data from the Genetics of Lipid Lowering Drugs and Diet Network, we identified genomic regions of relevance to fenofibrate response in a sample of 173 families. Our approach included a multipoint linkage scan, followed by selection of the families showing evidence of linkage. We identified a strong signal for changes in LDL-cholesterol (LDL-C) on chromosome 7 (peak logarithm of odds score=4.76) in the full sample ( n =821). The signal for LDL-C response remained even after adjusting for baseline LDL-C. Restricting analyses only to the families contributing to the linkage signal for LDL-C ( N =19), we observed a peak logarithm of odds score of 5.17 for chromosome 7. Two genes under this peak ( ABCB4 and CD36 ) were of biological interest. These results suggest that linked family analyses might be a useful approach to gene discovery in the presence of a complex (e.g. multigenic) phenotype.